2021
DOI: 10.1021/jacs.1c01138
|View full text |Cite
|
Sign up to set email alerts
|

Merging NiH Catalysis and Inner-Sphere Metal-Nitrenoid Transfer for Hydroamidation of Alkynes

Abstract: The formal hydroamination/hydroamidation utilizing metal hydride is an appealing synthetic tool for the construction of valuable nitrogen-containing compounds from unsaturated hydrocarbons. While significant advances have been made for the functionalizations of alkenes in this realm, the direct hydroamidation of alkynes remains rather limited due to the high feasibility of the key metal-alkenyl intermediate to choose other reaction pathways. Herein, we report a NiH-catalyzed strategy for the hydroamidation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
68
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 91 publications
2
68
1
Order By: Relevance
“…When 2,9-dibutyl-1,10-phenathroline ( L4 ) was utilized as the ligand, a highly γ selective methylene C­(sp 3 )–H amidation (up to 24:1 rr) was achieved in up to 90% yield (>40 examples). Recently, dioxazolones have emerged as versatile reagents for transition-metal-catalyzed hydroamidation . However, the use of dioxazolones in NiH-catalyzed alkene functionalization is less established.…”
supporting
confidence: 88%
“…When 2,9-dibutyl-1,10-phenathroline ( L4 ) was utilized as the ligand, a highly γ selective methylene C­(sp 3 )–H amidation (up to 24:1 rr) was achieved in up to 90% yield (>40 examples). Recently, dioxazolones have emerged as versatile reagents for transition-metal-catalyzed hydroamidation . However, the use of dioxazolones in NiH-catalyzed alkene functionalization is less established.…”
supporting
confidence: 88%
“…A NiH-catalyzed strategy for the hydroamidation of alkynes with dioxazolones was developed by our group most recently, 75 which allowed convenient access to synthetically useful secondary enamides with either (E)-anti-Markovnikov or Markovnikov selectivity by the choice of bipyridine (bpy) ligands. In that study, H 2 O was found to be an essential component for high catalyst turnovers (Scheme 40).…”
Section: Utilization Of Dioxazolones In Cu and Ni Catalysismentioning
confidence: 99%
“…Compared with the widespread success of CuH catalytic systems in alkene functionalization, NiH catalysis is more commonly used in the hydrofunctionalization of alkynes probably due to the slow protodemetalation of alkenylnickel intermediates . Recently, Chang and Seo achieved the first NiH-catalyzed hydroamidation of alkynes with dioxazolones for the selective synthesis of enamides . Given the intrinsic reactivity of NiH complexes, we recently questioned whether a NiH catalytic system could be applied to further expand the research on hydroamination of simple alkynes which is a long-standing challenge in Cu or Co catalytic systems.…”
mentioning
confidence: 99%
“…These results strongly support that the expected hydroamination completely outcompetes the semireduction process in this NiH catalytic system. Compared with the easy protonation of well-established alkenylcopper intermediates, the protodemetalation of the alkenylnickel species is unfavorable because of the relatively high energy barrier …”
mentioning
confidence: 99%